x平方-x+1=x平方-x分之6
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 05:45:35
x平方-x+1=x平方-x分之6x平方-x+1=x平方-x分之6x平方-x+1=x平方-x分之6x平方-x+1=x平方-x分之6-x+1=-x分之6x-x分之6-1=0x平方-x-6=0(x-3)(x
x平方-x+1=x平方-x分之6
x平方-x+1=x平方-x分之6
x平方-x+1=x平方-x分之6
x平方-x+1=x平方-x分之6
-x+1=-x分之6
x-x分之6-1=0
x平方-x-6=0
(x-3)(x+2)=0
x-3=0,x+2=0
所以,x=3.x=-2
原式
-x+1=-x分之6
x-1=x分之6
x方-x=6
x方-x-6=0
(x-3)(x+2)=0
所以x=3或x=-2
x平方-x+1=x平方-x分之6
x平方+x分之7 + 1-x平方分之6=x-x平方分之1
x的平方+x分之7+x的平方-x分之1=x的平方-1分之6
x的平方+x分之7+x的平方-x分之1=x的平方-1分之6
x的平方+x分之7+x的平方-x分之1=x的平方-1分之6
解方程:x平方+x分之7+x平方-x分之3=x平方-1分之6
x的平方+x分之7-x的平方-1分之6+x的平方-x分之3=0
1.x平方-1分之x平方+x 2.x平方-6x+9分之x平方-9 化简
x的平方+2x-x的平方+2x分之6=1
x平方-x-x平方-x分之12=4
x平方-6x+8分之2,x平方+x-6分之1,12+x-x平方分之3-x尤其是x平方-6x+8,x平方+x-6,12+x-x平方
x-3分之x-x的平方-3x分之x+6+x分之1
x平方+6x+9分之x平方-1÷(1-x)×x平方+4分之x+3
x+1分之x的平方-6x+9除以x的平方+x分之x的平方-9
计算x平方—1分之x平方—5x+6除以x平方+x分之x—3
[(x分之x平方+4)-4]除x平方+2x分之x平方-4,其中x=负1
x平方+x分之4=x+1分之6-x分之1
x分之3+x-1分之6=x的平方-x分之7